Diseminasi Teknologi True Seed of Shallot dan Umbi Mini Bawang Merah di Karangploso, Malang, Jawa Timur - . Makhziah; Ida Retno Moeljani; Juli Santoso (Institut Pertanian Bogor, 2019)
Shallots (Allium cepa var. aggregatum) is one of the vegetable commodities whose demand continues to increase in line with population growth. The purpose of this community service program to disseminate the results of research on how to produce true seed of shallot (TSS) then plant TSS to produce mini bulbs as seeds of shallots. The target audience was the farmers group Tani Mulya in Tawangargo Village, Karangploso Sub-District, Malang Regency, East Java. Activities step included preparation, socialization, demonstration plot of shallot bulbs planting to produce TSS and planting TSS, to produce mini bulbs as seeds of shallot. Batu Ijo variety grown to produce TSS, while planting of TSS used Tri Sula and Keta Monca varieties. This activitity was done well according to a Likert scale of 4.3 (good category = 4–4.9). Farmers were able to adopt the technology of TSS production and planting of TSS to produce shallot mini bulbs of seeds, with indication of the production of TSS and mini bulbs. The flowering of shallot plants 55.5 and TSS seed weight 10.16 g/m2. Bulbs seed of Batu Ijo variety produced large bulbs, while TSS from Tri Sula and Keta Monca varieties produced mini bulbs that can be used as seeds. The change of the shallot seeds technology from bulbs to TSS will be economically beneficial, because the TSS required less than bulbs, so the cost difference is quite large. TSS needs 3–5 kg/ha (TSS price IDR 1.200.000/kg), and bulbs seed needs 1–1.5 ton/ha (bulbs price IDR 30.000/kg), so the margin is IDR 24.000.000 per hectare.